Phase Uniformly Distributed Circular MQAM Combined With Probabilistic Shaping for PM-CO-OFDM Systems in Satellite-to-Ground Optical Communications - Huan Chen; Tao Yang; Liqian Wang; Xue Chen; Lei Zhang; Zhiguo Zhang (IEEE Photonics Journal)
Due to the rapid growth of high-resolution services, low earth orbit satellite-to-ground (LEO-StG) optical communications are expected to provide higher speed and better receiver sensitivity transmission. Here, we propose a phase uniformly distributed circular m-ary quadrature amplitude modulation (MQAM) combined with probabilistic shaping (PS) scheme for polarization multiplexing coherent optical orthogonal frequency-division multiplexing (PM-CO-OFDM) systems in LEO-StG communications to achieve high capacity transmission and improve receiver sensitivity as well as linewidth tolerance. In such scheme, the radius ratio of the circular 16/32QAM is optimized to maximize the minimum Euclidean distance (MED), and the constellation points of each ring are uniformly distributed to maximize the phase space of adjacent constellation points. Besides, the circular 16/32QAM is combined with probabilistic shaping (PS) to further increase the MED under the constraint of average transmit power. Simulation results of such circular 16/32QAM combined with PS scheme under different turbulence channels not only demonstrate its feasibility, but also show the improvements in receiver sensitivity and linewidth tolerance compared with regular 16/32QAM under same entropy. The improvement of receiver sensitivity is also experimentally validated. The superiorities of such scheme make it highly desirable for potential application in long-reach, non-relay, and high capacity LEO-StG optical communications .